Lao PDR Investment Climate Assessment 2014 : Policy Uncertainty in the Midst of a Natural Resources Boom - World Bank Group (Washington, DC, 2015)
The World Bank undertakes periodic Investment Climate Assessments in order to provide policymakers with a better understanding of how the private sector is performing and where the principal constraints to increased private sector investment are to be found. These assessments are informed by Enterprise Survey that follow a standardized approach and are conducted with the objective of providing detailed information on firm-level performance and constraints. So far, Enterprise Surveys have been conducted in more than 135 different countries and capturing data from over 130,000 individual businesses. This is the third Investment Climate Assessment carried out in Lao PDR, and builds on findings from the previous assessments carried out by the World Bank in 2007 and 2011, each of which was in turn informed by an Enterprise Survey. This 2014 Investment Climate Assessment (ICA) is based on an Enterprise Survey undertaken across Loa PDR for the World Bank in late 2012. The survey covered nearly 400 formal private firms across six provinces, including small, medium-sized and large firms. Half of the businesses surveyed were in manufacturing and half in services. The World Bank Enterprise Surveys are the only firm-level data collected in Lao PDR that use stratified random sampling, and thus allow for results from the sample to be considered statistically representative of the entire Lao private sector. It is also the only Enterprise Survey in the country that captures detailed firm performance data on sales and cost of sales, from which aggregate estimates of firm level profitability and productivity can be computed. The economy of Lao PDR has been growing rapidly based principally on the development of natural resource based industries. The transformation of natural wealth in terms of the country s mineral and water resources has propelled high rates of investment and economic expansion for more than a decade. Lao PDR has become a middle income economy and the country has achieved success in reducing poverty and delivering improved public service the natural resource development process has also created spillover effects, mostly notable via strong expansion in the services and construction domestic private sectors.